2005
DOI: 10.1002/cncr.21276
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of BRCA1 pathogenic and BRCA1/BRCA2 unclassified variant mutations in patients with ovarian carcinoma

Abstract: BACKGROUNDThe clinical relevance of BRCA1/2 alterations in ovarian carcinoma patients is debatable. Our aim was to determine factors influencing the risk of recurrence and death in ovarian carcinoma patients with BRCA pathogenic and unclassified variant mutations.METHODSA consecutive series of 205 women with primary ovarian carcinoma were screened for mutations in BRCA1 and BRCA2 genes using a conformational sensitive gel electrophoresis and direct sequencing. Data regarding medical and familial history were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 21 publications
4
38
1
1
Order By: Relevance
“…Our results also suggest that cells with defects in the BRCA pathway may be more responsive to treatment with cisplatin than BRCA1/ 2-proficient cells. Indeed, clinical results support that patients with defects in BRCA1 or BRCA2 have better responses to platinum-based therapies than patients with BRCA1/2 intact (10,39,45). The ability to perform genome-scale siRNA screens in cells of different genetic backgrounds in the presence of different combinations of approved chemotherapeutic drugs may provide a rational way to guide clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also suggest that cells with defects in the BRCA pathway may be more responsive to treatment with cisplatin than BRCA1/ 2-proficient cells. Indeed, clinical results support that patients with defects in BRCA1 or BRCA2 have better responses to platinum-based therapies than patients with BRCA1/2 intact (10,39,45). The ability to perform genome-scale siRNA screens in cells of different genetic backgrounds in the presence of different combinations of approved chemotherapeutic drugs may provide a rational way to guide clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…No differences in response to chemotherapy was also observed in a large Norwegian follow-up study [8,11,15].…”
Section: Discussionmentioning
confidence: 65%
“…The literature lacks reports on patients of East Central Europe origin, different in genetic regard as mentioned before. The only report on the outcome of the treatment in Polish BRCA1-OC patients was presented in 2005 by Majdak et al; however, it included only 18 cases [8]. Results presented in the report should be analysed, taking into account limitations of the study material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies have observed no significant difference (5,6), several studies have now demonstrated that BRCA1 or BRCA2 germline mutation confers an improved prognosis in terms of overall survival compared to sporadic disease (7)(8)(9)(10)(11)(12)(13)(14)(15). As both BRCA1 and BRCA2 are known to play roles in the repair of DNA by homologous recombination, one possibility is that the improved survival observed in BRCA-deficient EOC is secondary to increased sensitivity to platinum-based therapy, since homologous recombination is critical to the repair of DNA-damage caused by the cross-linking effects of platinum.…”
Section: Introductionmentioning
confidence: 99%